Metafora dalam Novel Namaku Alam - Damayanti, Annisa; Mayasari, Mayasari; Arindawati, Weni A. (Kajian Linguistik dan Sastra, 2025)
The novel Namaku Alam tells the story of the descendants of political prisoners who receive discrimination and negative stigma from society. The purpose of this study is to describe the use of metaphors in the novel Namaku Alam through the text dimension, the production process of Namaku Alam through the dimension of discourse practices, and the socio-culture of Indonesian society through socio-cultural practices. This research uses qualitative method and critical discourse analysis of Norman Fairclough model. In the text dimension, researchers found 15 metaphorical expressions containing elements of discrimination against descendants of political prisoners in the novel Namaku Alam. In the discursive practice dimension, it is known that the author's background as a journalist influences Leila in writing and this novel is also considered suitable for Gen Z people based on reader reviews. The socio-cultural dimension that influences this text consists of the research process carried out by the author, Leila's work, the principles of KPG publishers, changes in the political system, and the discrimination against descendants of political prisoners in society. Abstrak Novel Namaku Alam mengisahkan keturunan tahanan politik yang mendapatkan diskriminasi dan stigma negatif dari masyarakat. Tujuan dari penelitian ini mendeskripsikan penggunaan metafora dalam novel Namaku Alam melalui dimensi teks, proses produksi Namaku Alam melalui dimensi praktik kewacanaan, dan sosial budaya masyarakat Indonesia melalui praktik sosio-budaya. Penelitian ini menggunakan metode kualitatif dan analisis wacana kritis model Norman Fairclough. Pada dimensi teks, peneliti menemukan 15 ungkapan metafora yang mengandung unsur diskriminasi terhadap keturunan tahanan politik dalam novel Namaku Alam. Pada dimensi praktik diskursif diketahui bahwa latar belakang pengarang  sebagai jurnalis mempengaruhi Leila dalam menulis serta novel ini juga dinilai sesuai untuk kalangan Gen Z berdasarkan ulasan pembaca. Dimensi sosio-budaya yang mempengaruhi teks ini terdiri dari proses riset yang dilakukan pengarang, pekerjaan Leila, prinsip penerbit KPG, perubahan sistem politik, serta masih terjadinya diskriminasi terhadap keturunan tahanan politik dalam masyarakat.